Constructing multiple heterogeneous interfaces in the composite of bimetallic MOF-derivatives and rGO for excellent microwave absorption performance. (March 2021) - Zhao, Yazhen; Wang, Wei; Wang, Junnan; Zhai, Junjian; Lei, Xiaoyi; Zhao, Wu; Li, Jiangnan; Yang, Haowen; Tian, Jiangxiao; Yan, Junfeng
Abstract: Metal nanoparticles exposed to air are easily oxidized and their impedance matching characteristics are poor, which leads to bad stability and poor absorption performance of electromagnetic waves (EMWs). In this work, ZIF-67@CoNi Layered Double Hydroxides grown onto GO (ZIF-67@CoNi LDHs-GO) was used as a precursor to prepare a hollow granatohedron structure consisting of CoNi nanoparticles embedded within nanoporous N-doped carbon polyhedrons (NCPs) grown onto rGO (CoNi@NCPs-rGO). The results show that rGO plays an important role in enhancing the EMWs absorption performance to a large extent. Typically, the optimal minimum reflection loss (RL) of compounds is −58.2 dB at 10.62 GHz with an absorber thickness of 2.5 mm, and the effective absorption bandwidth (EAB, RL < −10 dB) is 4.03 GHz (8.80–12.83 GHz) with a filler loading of 30%. Particularly, with a matching thickness in the 2–5 mm range, the EAB can reach a value of up to 12 GHz. The synergism between the dielectric loss of rGO and nanoporous NCPs and the magnetic loss of CoNi nanoparticles, as well as the optimized impedance matching properties and multiple reflection losses from rGO and NCPs, contribute to the observed enhanced absorption performance. Graphical abstract: Image 1 Highlights: Successfully fabricated CoNi@NCPs-rGO through a simple strategy. Enhanced impedance matching and multiple reflection losses are achieved. CoNi@NCPs-rGO shows an excellent absorption (RLmin −58.2 dB, EAB 4.03 GHz).